Differential effects of behavioral interventions with a graded physical activity component in patients suffering from Chronic Fatigue (Syndrome): An updated systematic review and meta-analysis. (August 2015) - Marques, M.M.; De Gucht, V.; Gouveia, M.J.; Leal, I.; Maes, S.
Abstract: An updated systematic review and meta-analysis was conducted to (1) evaluate the effects of behavioral and psychological interventions containing a graded physical activity component upon fatigue severity, physical functioning, physical activity and psychological distress, and to (2) examine potential moderator effects of trial characteristics (type of control, setting, provider, length of treatment, psychological component, flexibility in physical activity, and minimal face to face patient–provider contact). Pertinent content of selected studies was extracted and rated on a scale of methodological quality. Sixteen randomized controlled trials (N = 2004) were included in the meta-analyses. Significant small to medium effect sizes (Hedge's g  = 0.25 to g  = 0.66) were found for all outcomes at post-treatment (M = 5.2 months) and follow-up (M = 11.7 months), with the exception of physical activity at post-treatment ( g  = 0.11). The largest effects were found for fatigue severity ( g  = 0.61 to g  = 0.66). Subgroup analyses revealed that minimal contact interventions had additional beneficial effects upon fatigue ( g  = 0.96) and depression ( g  = 0.85). Interventions provided by psychologists-psychotherapists and interventions conducted in secondary–tertiary settings also resulted in more beneficial effects on fatigue. We found some indication of publication bias. The small number of studies and variability between them are limitations of this study. Future research should explore additional moderating effects in order to improve the effectiveness of interventions. Highlights: Interventions including physical activity have beneficial effects on chronic fatigue. The number of trials is modest and there is heterogeneity between them. Type of setting and provider of treatment moderate fatigue severity effect sizes. Minimal direct contact interventions are promising.